2019
DOI: 10.1038/s41598-018-37033-4
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomics analysis of host liver and meta-transcriptome analysis of rumen epimural microbial community in young calves treated with artificial dosing of rumen content from adult donor cow

Abstract: In mammals, microbial colonization of the digestive tract (GIT) occurs right after birth by several bacterial phyla. Numerous human and mouse studies have reported the importance of early gut microbial inhabitants on host health. However, few attempts have been undertaken to directly interrogate the role of early gut/rumen microbial colonization on GIT development or host health in neonatal ruminants through artificial manipulation of the rumen microbiome. Thus, the molecular changes associated with bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 80 publications
(99 reference statements)
2
23
0
Order By: Relevance
“…In contrast, the period of early ruminal development shows potential to be a favorable time to manipulate and direct the rumen environment (Yáñez-Ruiz et al, 2015). Directfed microbials, early nutrition, and artificial dosing with ruminal contents from adults have been utilized as strategies to direct the microbial ecology of the gastrointestinal tract of young ruminants and subsequent production performance (Schönhusen et al, 2003;Ishaq et al, 2015;Fouladgar et al, 2016;Zhang et al, 2017;Li et al, 2019). Li and co-authors found that separate ruminal wall microbial communities formed between dairy calves dosed with and without adult-derived rumen fluid (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the period of early ruminal development shows potential to be a favorable time to manipulate and direct the rumen environment (Yáñez-Ruiz et al, 2015). Directfed microbials, early nutrition, and artificial dosing with ruminal contents from adults have been utilized as strategies to direct the microbial ecology of the gastrointestinal tract of young ruminants and subsequent production performance (Schönhusen et al, 2003;Ishaq et al, 2015;Fouladgar et al, 2016;Zhang et al, 2017;Li et al, 2019). Li and co-authors found that separate ruminal wall microbial communities formed between dairy calves dosed with and without adult-derived rumen fluid (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, 8 young bull calves were randomly assigned into two groups: (1) control group (Con; supplemented with autoclaved rumen content, n = 4) and (2) treatment group (HE; supplemented with inocula from the HE donor cow, n = 4). As mentioned in the paper of Li et al [ 23 ], the control inocula were prepared by autoclaving the combined inocula (50% from each) from the HE donor cow and the LE donor cow. Experiment was carried out from birth to 56 days.…”
Section: Methodsmentioning
confidence: 99%
“…Experiment was carried out from birth to 56 days. The inocula was administered within 3 days after birth, then at 2, 4, and 6 weeks following the initial dosing [ 23 ]. Until 8 weeks of age, the 4 calves in each group were sacrificed and the abomasum tissues were collected immediately after euthanization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations